2022
DOI: 10.3390/horticulturae8020176
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Transcriptomic Analysis Provides Insight into the Key Regulatory Pathways and Differentially Expressed Genes in Blueberry Flower Bud Endo- and Ecodormancy Release

Abstract: Endodormancy is the stage that perennial plants must go through to prepare for the next seasonal cycle, and it is also an adaptation that allows plants to survive harsh winters. Blueberries (Vaccinium spp.) are known to have high nutritional and commercial value. To better understand the molecular mechanisms of bud dormancy release, the transcriptomes of flower buds from the southern highbush blueberry variety “O’Neal” were analyzed at seven time points of the endo- and ecodormancy release processes. Pairwise … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 66 publications
0
2
0
Order By: Relevance
“…Recent evidence strongly supports the notion that the accumulation of chilling triggers a significant downregulation of the ethylene content. Additionally, it has been observed that the expression levels of ERFs and BRC1 also decrease under chilling conditions [ 19 , 27 ]. In our study, we observed a similar trend, with the expression of VcTCP18 decreasing and the ability of flower buds to break being enhanced.…”
Section: Discussionmentioning
confidence: 99%
“…Recent evidence strongly supports the notion that the accumulation of chilling triggers a significant downregulation of the ethylene content. Additionally, it has been observed that the expression levels of ERFs and BRC1 also decrease under chilling conditions [ 19 , 27 ]. In our study, we observed a similar trend, with the expression of VcTCP18 decreasing and the ability of flower buds to break being enhanced.…”
Section: Discussionmentioning
confidence: 99%
“…Endodormancy is a phase during which perennial plants prepare for the next seasonal cycle, as well as an adaptation that allows the plants to survive harsh winters. The aim of Yongqiang Li's [7] study was to comprehend the underlying molecular mechanisms of bud dormancy release in blueberries (Vaccinium spp.). The transcriptomes of the flower buds were examined at seven dormancy stages.…”
mentioning
confidence: 99%